The Effect of Benson Relaxation on Anxiety Levels In Major Surgical Preoperative Patients - Setiyono, Agus; Sari, Yeni Kartika; Pribadi, Yohanes Kusuma (Health Gate, 2023)
Surgery can cause excessive fear and anxiety and can lead to complications. To reduce anxiety, non-pharmacological techniques is Benson Relaxation Therapi which is carried out by deep breathing and accompanied by beliefs held by the patient to achieve a relaxed state. Population on this research is preoperative major surgery patients. Sampling technique with Purposive Sampling 22 respondent. This research method : Quasy Experimental with One Group Pre-Test Post-Test, using questionnaire sheets, Standard Operating Procedures of Benson’s Relaxations, and Wilcoxon Sign Rank Test analysis.  The purpose of study to determine the effect of Benson’s Relaxations on anxiety levels in preoperative major surgery patients. The Results of the Study : Using the analysis with the results of p-value = 0.000 which means <0.005. Conclusion : There is an effect of Benson’s Relaxation on the anxiety levels of pre operative major surgery patients. With the result of  this reseach be used as a reference  for Mardi Waluyo Blitar District Hospital in publishing of SPO Benson’s Relaxation it can be used to treat anxiety non-pharmacologically. Beside that, of nurses are expected to be able and willing to implement of Benson’s Relaxation which is proven effective in treating anxiety patients in all patients who experience anxiety in general.Keywords : Surgery, Benson Relaxation Technique, Anxiety